Legal Policy of the Indonesian Government to Achieve Net Zero Emissions - Vikram Surya Husada; Iwan Erar Joesoef (Journal Research of Social Science, Economics, and Management, 2022)
In 2016, Indonesia is a country that has agreed to the contents of the Paris Agreement. The contents of the Paris Agreement have been ratified into Indonesian law number 16 of 2016. The Indonesian government is targeting to achieve Net Zero Emissions by 2060. This study aims to achieve Net Zero Emissions by 2060, the Indonesian government is committed to reducing emissions by 29% (without conditions) or 41% (conditional) in 2030, which can be achieved by encouraging the use of new and renewable energy (EBT) by 23% by 2025. This study uses normative juridical methods to review policies and improve regulations for the Net Zero Emissions program by obtaining existing literature, theories, concepts, principles, and rules related to the legal perspective. Appropriate and consistent energy policies, including a long-term strategy to increase the use of new and renewable energy, are needed to achieve emission reduction targets. Policies made by the Indonesian government should reduce fossil fuels, develop environmentally friendly technologies and start increasing the use of new and renewable energy. It is very important to strengthen carbon emission reduction policies by considering all aspects to achieve the goal of 2060 without carbon emissions